A Retrospective Cohort Study of Treatment Outcomes of Adult Patients With Relapsed or Refractory Follicular Lymphoma (ReCORD-FL). Issue 7 (21st July 2022) - Salles, Gilles; Schuster, Stephen J.; Fischer, Luca; Kuruvilla, John; Patten, Piers E. M.; von Tresckow, Bastian; Smith, Sonali; Ubieto, Ana Jiménez; Davis, Keith L.; Nagar, Saurabh; Zhang, Jie; Bollu, Vamsi; et al.
Abstract : This study (ReCORD-FL) sought to construct a historical control cohort to augment single-arm trials in relapsed/refractory follicular lymphoma (r/r FL). A retrospective study in 10 centers across North America and Europe was conducted. Adults with grade 1–3A FL were required to be r/r after ≥2 therapy lines including an anti-CD20 and an alkylator. After first becoming r/r, patients were required to initiate ≥1 additional therapy line, which defined the study index date. Endpoints were observed from start of each therapy line (including index line) until death, last follow-up, or December 31, 2020. Endpoints were complete response (CR) rate, overall response rate (ORR), time to next treatment or death (TNT-D), event-free survival (EFS), and overall survival (OS). One hundred eighty-seven patients were identified. Most patients' (80.2%) index therapy occurred in third line (3L) (range, 3L–6L). Median follow-up from FL diagnosis was 9 years (range, 1–21 years). CR and ORR to the index therapy were 39.0% and 70.6%, respectively. Median (95% confidence interval) EFS from index was 14.6 (11.0-18.0) months; median OS from index was 10.6 years. Outcomes worsened across successive treatment lines and for patients who were double refractory (r/r to both an anti-CD20 monoclonal antibody and an alkylator) or POD24 (progressed ≤24 months after front-line anti-CD20) at index. Findings demonstrate the unmet need of FL patients with multiply relapsed, double refractory, or POD24 disease. Based on robustness of the historical data collected and comparability with a previous study (SCHOLAR-5), ReCORD-FL presents a valuable source of control data for comparative studies in r/r FL.